1987
DOI: 10.1073/pnas.84.21.7562
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in DNA repair in mouse lymphoma strain L5178Y-S.

Abstract: The production and repair of radiation-induced DNA damage were measured by filter elution in strains of mouse lymphoma L5178Y cells differing in their sensitivity to ionizing radiation. The induction of radiation-induced damage, as measured by filter elution at pH 12.1, 9.6, and 7.2, was similar in the resistant-strain LY-R and the sensitive strain LY-S. The repair of single-strand breaks and alkali-labile sites, as measured by filter elution at pH 12.1 at various times after irradiation, was somewhat slower i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Detailed comparison of their properties and analysis of the differences related to their responses to ionizing radiation have been carried out. The central problem has been that of DNA damage and repair, consecutively studied with the methods of alkaline sedimentation (Korner et al 1977), alkaline unwinding (Johanson et al 1982), alkaline and neutral filter elution Hittelman 1987, 1988 a, b;Evans et al 1987), and fluorescent halos (Kapiszewska et al 1989). With the exception of alkaline sedimentation, no analyses carried out at denaturing conditions have revealed differences either in the initial DNA damage or in its repair.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Detailed comparison of their properties and analysis of the differences related to their responses to ionizing radiation have been carried out. The central problem has been that of DNA damage and repair, consecutively studied with the methods of alkaline sedimentation (Korner et al 1977), alkaline unwinding (Johanson et al 1982), alkaline and neutral filter elution Hittelman 1987, 1988 a, b;Evans et al 1987), and fluorescent halos (Kapiszewska et al 1989). With the exception of alkaline sedimentation, no analyses carried out at denaturing conditions have revealed differences either in the initial DNA damage or in its repair.…”
Section: Discussionmentioning
confidence: 98%
“…The earlier finding of slower repair of DNA strand breaks [alkaline sedimentation (Korner et al 1977)] was treated with some reservation because of the high (100 Gy) radiation dose applied. When DNA damage was analyzed at denaturing pH [alkaline unwinding (Johanson et al 1982); alkaline elution (Wlodek an Hittelman 1987;Evans et al 1987)], no difference between LY-R and LY-S cells was found in either the initial damage or its repair.…”
Section: Discussionmentioning
confidence: 98%
“…1974, Painter and Young 1980, Scott and Zampetti-Bosseler 1982 . A third property is a reduced capacity to rejoin DNA strand breaks which has been reported for L5178Y S/S cells (Ueno et al 1979a,b, Golden et al 1980, Evans et al . 1987, Wlodek and Hittelman 1987 .…”
Section: Introductionmentioning
confidence: 94%
“…The xrs, XR-1 and L5178Y-S mutants have been reported to show defective double-strand break (dsb) rejoining (Kemp et al, 1984;Giaccia et al, 1985;Evans et al, 1987;Wlodek & Hittelman, 1987) measured by neutral filter elution. The irs mutants have no measurable impairment of dsb rejoining, but irsl was found to have low repair fidelity compared with its parent line, V79, using plasmid reconstitution (Debenham et al, 1988b).…”
mentioning
confidence: 99%